Explaining Indonesia's relations with Singapore during the new order period : the case of regime maintenance and foreign policy - Lee, Terence Chek Liang (2009)
This paper explores the nature of Indonesia's relations with Singapore during former President Suharto's New Order period (circa 1965-1998). This paper argues that Indonesia's foreign relations with Singapore during the New Order period not only improved but took on a more conciliatory and co-operative countenance since Suharto assumed power in 1966 because there was a belief that relations with Singapore could be useful in serving the Suharto regime's interests. Specifically, Indonesia's biateral relationship with Singapore and the co-operative activities between the two countries were means of external support for the Suharto government in the face of periodic domestic political challenges. Indonesia's diplomatic relations with Singapore were essentially motivated by former President Suharto's belief that the bilateral relationship could reinforce his hold on power, i.e. regime maintainance.